Fraud Problems in International Company Financial Reports - Achmad Bagas Djuan Rajendra; Joshua Yonathan Sugianto; Hwihanus Hwihanus (International Journal of Economics, Commerce, and Management, 2024)
This research aims to determine the factors that cause fraud in financial reporting by reviewing literature relating to false financial reporting in agencies or organizations, especially in the scope of public work. The population used is financial reporting at several international companies in 2019-2024. The data analysis technique uses comparative analysis where the researcher compares 2/more objects to find out the differences and similarities in a study by applying a meta study to explain the analysis of previous research results. The sample in the research used a purposive sampling method where sampling was based on the author's considerations. The results show that the occurrence of fraud/fraud in financial statements is caused by several factors in accordance with the fraud triangle theory where there are 3 factors that cause individuals/groups to commit fraud/cheating, namely pressure, opportunity, and justification/rationalization so that a person/group assumes that fraud is a normal action and occurs in many companies.